Enhancing Students’ Speaking Ability Through Small Group Discussion Technique to the Firts Year Students of SMA Negeri 1 Ratahan - Mogea, T (Universitas Negeri Manado, 2019)
This research in intended to find out the effectiveness of small group discussion technique in improving the students’s speaking ability. It was conducted at SMA Negeri 1 Ratahan in which one class of the first-year students of the school was the sample. The data of the research were obtained by using test in the form of pre-test and post-test. The result showed that the scores of the post-test were higher than that of the pre-test. The mean of the post-test is 8.2 and the mean of the pre-test is 6.7. Teaching speaking skill by using small group discussion technique can improve the students’ ability in speaking. Small group discussion technique can give the students opportunity to practice their language. In small group discussion, they can express their ideas and thought freely. It will be better for English teacher to vary the techniques of teaching to avoid boredom that might appear to the students. Keywords: Speaking abiliy; Technique; Small group discussion